Larval chaetotaxy and morphometry of Oosternum costatum (Coleoptera: Hydrophilidae) including a discussion of larval characters with phylogenetic relevance - Archangelsky, Miguel (2018)
The primary and secondary chaetotaxy of the head capsule and head appendages of the first and third larval instars of Oosternum costatum (LeConte, 1855) (Coleoptera: Hydrophilidae: Sphaeridiinae, Megasternini) are described for the first time. Morphometric characters derived from the head capsule and mouthparts are included, together with detailed illustrations of all characters. The morphology and chaetotaxy of these larvae is compared to that of other larvae of the tribe Megasternini, confirming that chaetotaxy is a useful source of characters for phylogenetic analyses. Comparative notes with Sphaeridium Fabricius, 1775 (Sphaeridiini) are also included.